Forças manuais e o design de produtos: uma revisão - Razza, Bruno Montanari; Paschoarelli, Luis Carlos [UNESP]; Lucio, Cristina do Carmo (My University, 2010)
Object manipulation is common in most daily living activities and many products and tasks require the application of large hand strength. The great incidence of injuries and accidents related to manual activity is a result of the lack of reliable and consistent parameters to design more efficient products. The aim of this paper was to review studies related to hand strength and indicate the characteristics and variables that have influence on the occupational tasks and everyday activities. Among those characteristics, we highlight the body posture and the positioning of various body segments as factors that may reduce the force, such as wrist deviation or inadequate postures. The type of grip was also widely investigated, resulting that handgrip can exert more force than pinch grips. In rotary strength evaluations, the flexion and extension movements of the wrist are generally stronger than pronation-supination. In general, cylindrical objects or those which have smooth surface finish are less effective in activities where greater strength is required. These considerations highlight the importance of knowing the variables related to manual activities, and indicate the need to investigate further the hand-object interface in both occupational and everyday activities.

A manipulação de objetos faz parte da maior parte das atividades da vida diária e muitos produtos e tarefas exigem grandes aplicações de força manual. Os índices elevados de lesões e acidentes relacionados a essa atividade é resultado, dentre outros fatores, da falta de parâmetros para a produção de produtos mais adequados. O objetivo deste estudo foi revisar as pesquisas realizadas sobre forças manuais e indicar as características e variáveis que influenciam a realização de atividades ocupacionais e cotidianas. Dentre os diversos fatores analizados, destaca-se a postura corporal e os posicionamentos dos diversos segmentos corporais, como por exemplo a redução da força gerada com o punho em posições não-neutras. O tipo de preensão também foi bastante investigado, sendo que as preensões palmares permitem realizar maior força que as preensões digitais. Em avaliações de torque, os movimentos de flexo-extensão do punho são, em geral, mais fortes que os de prono-supinação. De forma geral, os objetos circulares ou que apresentam acabamento superficial muito liso são menos efetivos em ações onde é necessária maior força. Essas considerações destacam a importância de se conhecer as variáveis relacionadas às atividades manuais, e indicam a necessidade de investigar mais detalhadamente a interface mão-objeto em atividades funcionais tanto ocupacionais quanto cotidianas.
Hand strength and the product design: a review
Keywords: Design; Ergonomics; Biomechanics; Hand strength; Grip; Design; Ergonomia; Biomecânica; Forças manuais; Preensão